Development strategy of Bangladesh - Islam, Nurul (New York : Oxfort Eng ; Pergamon Press, 1978)
This monograph is an attempt to explore the essential components of a development strategy for Bangladesh. The study draws upon the lesson of past experience, especially the experience with development policies and problems in the post independence period.
Includes bibliographical references and index.
hza 27/06/2018
Loans
Keywords: Economic policy; Bangladesh